A modern interpretation of the history of the Pleistocene glacial cycles - V. M. Kotlyakov; D. M. Sonechkin (Лëд и снег)
One of the, Glaciological descriptions of Greenland and Antarctica were among the most outstanding events in the geographical investigations of the Earth, made in the 20th century. They have shown that glaciations, traces of which were found in Europe and North America in the first half of the 19th century, waxed and waned during the Pleistocene repeatedly and were synchronous with the expansions and reductions of the Antarctic ice sheet. Further analyses of the sea-bed sediments confirmed the fact of such synchronicity, and revealed that the durations of the Pleistocene glacial cycles (on the order of one hundred thousand years) were significantly longer then approximately forty thousand years alternations of the warm and cold climate conditions during the preceding Pliocene. In this paper, using wavelets, and methods of the theory of the nonlinear dynamical systems, patterns of the Pleistocene’s and Pliocene’s cyclic variations of climate are compared with each other, to understand the mechanisms which can be responsible for their excitation and evolution.